2017
DOI: 10.1021/acs.jpca.6b12724
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the Ring-Puckering Vibrational Mode in Thietane Cation

Abstract: We have measured the high-resolution vibrational spectra of a thietane (trimethylene sulfide) cation in the gas phase by employing the vacuum ultraviolet mass-analyzed threshold ionization (VUV-MATI) spectroscopic technique. Peaks in the low-frequency region of the observed MATI spectrum of thietane originate from a progression of the ring-puckering vibrational mode (typical in small heterocyclic molecules), which is successfully reproduced by quantum-chemical calculations with 1D symmetric double-well potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Although the uncertainty in the position measurements was approximately 1 cm −1 , a larger error of ±3 cm −1 is expected based on the previous measurements of other molecules. [27][28][29]31 Comparing the ionization energy value (9.7068 ± 0.0017 eV) of cyclopentanone determined by our previous VUV photoionization experiments, 36 we found that the presence of a double bond in 2CP results in a lowered ionization energy. Such a result can be attributed to the HOMO consisting of nonbonding orbitals on the oxygen atom in the carbonyl group interacting with the σ orbitals in the molecular plane, similar to methyl vinyl ketone with the acrolein moiety, 41 as will be discussed later.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Although the uncertainty in the position measurements was approximately 1 cm −1 , a larger error of ±3 cm −1 is expected based on the previous measurements of other molecules. [27][28][29]31 Comparing the ionization energy value (9.7068 ± 0.0017 eV) of cyclopentanone determined by our previous VUV photoionization experiments, 36 we found that the presence of a double bond in 2CP results in a lowered ionization energy. Such a result can be attributed to the HOMO consisting of nonbonding orbitals on the oxygen atom in the carbonyl group interacting with the σ orbitals in the molecular plane, similar to methyl vinyl ketone with the acrolein moiety, 41 as will be discussed later.…”
Section: Resultsmentioning
confidence: 94%
“…Owing to the delayed ionization–extraction scheme, ZEKE and MATI techniques are the best fit for determining the cationic structures of various kinds of molecules in high resolution, whereas the PE does not give sufficiently high enough resolution for large polyatomic molecular cations. In particular, one-photon vacuum ultraviolet MATI (VUV-MATI) spectroscopy is greatly beneficial in yielding the accurate ion internal energy of a molecule originating from the zero-point level of a cation. The acquired VUV-MATI spectrum, which is essentially the vibrational spectrum of the cation, can then be analyzed using the Franck–Condon (FC) fitting method to obtain the precise cationic structure. In addition, information regarding the highest occupied molecular orbital (HOMO) of the neutral molecule can be obtained by examining the geometrical changes induced by ionization, which ultimately affects the vibrational spectrum of the corresponding cation according to the FC principle. Hence, this method is advantageous in elucidating the reliable structure of molecular cations.…”
Section: Introductionmentioning
confidence: 99%
“…The DA1OPTN Meinander–Laane potential energy program was used to fit the experimental data of Strauss and Gwinn for TMS and from Lee and coworkers for TMS + . The kinetic energy functions of eqs and were applied in the calculations, and the constants a and b in eq were adjusted to give the best least-squares fits.…”
Section: Calculationsmentioning
confidence: 99%
“…14 In general, information about an HOMO can be obtained by examining the geometrical changes induced by ionization, which can be extracted from the vibrational spectrum of the corresponding cation using the Franck-Condon (FC) principle. Recently, VUV mass-analyzed threshold ionization (MATI) spectroscopic investigations of four-, 15,16 five-, 17,18 and sixmembered [19][20][21][22] heterocycles showed well-resolved vibrational peaks in the full vibrational energy range for the corresponding cations. These spectra mostly consisted of symmetry-allowed fundamental bands.…”
Section: Introductionmentioning
confidence: 99%